Devil in disguise [large type] : the Ravenels meet the Wallflowers - Kleypas, Lisa (Harper Large Print, an imprint of HarperCollinsPublishers, 2021)
A strong-willed young widow running her late husband's shipping company, Lady Merritt Sterling avoids scandal until she meets a rough-and-tumble Scottish whisky distiller on the run from a very determined killer.